Environmental Pollution with Household Waste in Algerian Legislation and its Implications for Achieving Environmental Security - Belazzoug, Bilal; Amara, Naima (Journal of Legal Studies and Researches, 2022)
With the expansion of the circle of pollution, household waste and similar are considered one of the most dangerous pollutants that threaten the environment nowadays. The present study deals with household waste contribution to environmental pollution, and scrutinizes the ways to realize sustainable environmental security through creating a balance between the requirements of quality of life, economic development, and environmental protection.